The Influence Of Managerial Ownership, Profitability And Leverage On Financial Distress: (Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) 2016-2019) - Minanari MINANARI (Indonesia Strategic Sustainability, 2022)
Financial distress is the stage of declining financial condition that occurs in a company prior to bankruptcy or liquidation (Platt & Platt 2002). The company can get out of this financial difficulty if the company has a strong determination to keep running its business even though it is in financial difficulty, on the condition that the company must really manage finances very carefully, thoroughly and precisely if this can be appropriately maintained. This study aims to examine the effect of Managerial Ownership, Return On Equity, Debt to Assets Ratio and Current Ratio on Financial Distress. The research object is property and real estate companies listed on the Indonesia stock exchange in 2009 – 2019. The total sample used in the study is 14 companies. The method was purposive sampling and a total sample of 35 annual report data. The analysis technique used in this study was the classical assumption test and multiple regression analysis. Based on the results of the analysis show that the profitability ratio as measured by Return On Equity (ROE) has a positive effect and the leverage ratio as measured by the Debt to Asset Ratio (DAR) has a negative effect on financial distress. Meanwhile, managerial ownership has no effect on financial distress.